Desain Media Google Earth untuk Pembelajaran Geografi SMA Kelas X Materi Dinamika Hidrosfer - Nurhaydah, Nurhaydah; Maryati, Sri; Lahay, Rakhmat Jaya (-, 2025)
This study explores the design process of instructional media using Google Earth to support senior high school Geography learning on Hydrosphere Dynamics. The media was developed through a location-based approach that integrates satellite imagery, placemarks, interactive maps, and visual narration to present content in a contextual and exploratory way. The design process is aligned with the Merdeka Curriculum, structured around learning objectives, strategic location selection, and multimedia element integration. A storyboard was used to ensure continuity between visual and narrative components, allowing for a coherent and meaningful learning flow. The development demonstrates that geospatial-based learning media can foster relevant, engaging, and participatory educational experiences. This study is limited to the design phase; therefore, future research is needed to assess its effectiveness in enhancing student learning outcomes through classroom implementation.